Formulasi Sediaan Sabun Mandi Padat Dari Ekstrak Etanol Daun Kedondong (Spondias pinnata (L.f) Kurz) - Hasma Hasma; Erna Kadrianti (Journal Syifa Sciences and Clinical Research, 2022)
Healthy skin is an element of female beauty. The thing that supports it is with cosmetics. The rise of the "back to nature" lifestyle has increased public confidence in cosmetics with natural ingredients. Cosmetics with natural ingredients are claimed to be safer to use on the skin than cosmetics using synthetic chemical compounds. Research has been carried out with the title "Formulation of Solid Bath Soap from Ethanol Extract of Kedondong Leaves (Spondias pinnata (L.f) Kurz)". This study aims to determine whether the formulation of solid bath soap from Kedondong (Spondias pinnata (L.f) Kurz) Leaf Ethanol Extract meets the criteria for quality requirements of pH, water content and high foam. The extract concentrations used were F1(3.5), F2 (7) and F3 (10.5). From the results of the research that has been carried out, it is obtained that the solid soap preparations F1 (3.5), F2 (7) meet the quality criteria test for pH, water content and foam height both before and after the cycling test. While the soap in FIII (10.5) met the water content and high foam test, but did not meet the pH quality standard for solid soap. Based on the results of this study, it can be concluded that from the three formulas above, the soap in FI and FII is a soap that meets the quality standard test of pH, water content and high foam. While the soap in FIII is soap that does not meet the required solid soap pH quality standard.